Heading stabilization of a mecanum wheel mobile robot using Kalman filter and SMC under variation condition - Ardianto Syaifur Rohman; Tunjung Genarsih; Sihmaulana Dwianto; Nuzula Afianah; Salsabila Liandra Putri; Nurul Zainal Fanani; Mochamad Irwan Nari; Ahmad Rofi'i; Fendik Eko Purnomo; Syamsiar Kautsar; Angga Dwinanda; Alfan Ahmad Berlian (Universitas Ahmad Dahlan, 2026)
This paper presents a robust heading stabilization system for a mecanum wheel mobile robot by integrating a Kalman filter (KF) with sliding mode control (SMC). A two-state KF estimates the robot’s heading angle and gyroscope bias from ICM20948 inertial measurement unit (IMU) measurements, reducing sensor noise by 65% and compensating for bias drift of 0.3° per second. The estimated heading is regulated using SMC with a boundary layer to minimize chattering. Implemented on a Raspberry Pi 3B, the system was validated under varying surface friction conditions and external disturbances. The controller achieved heading stabilization with root mean square error (RMSE) between 0.380° and 0.589° across all surfaces, steady-state error within ±0.5°, and convergence within 2.0–2.6 seconds. Under severe disturbances causing heading deviations up to 238°, rapid recovery within 0.5 seconds was achieved with only 3.04° final steady state error. The results demonstrate the feasibility of implementing robust heading stabilization on low-cost embedded platforms for autonomous navigation applications.